Assessment of the quantity of microorganisms associated with bronchiectasis in saliva, sputum and nasal lavage after periodontal treatment: a study protocol of a randomised controlled trial. Issue 4 (15th April 2016) - Pinto, Erika Horácio; Longo, Priscila Larcher; Camargo, Caroline Cristina Batista de; Dal Corso, Simone; Lanza, Fernanda De Cordoba; Stelmach, Rafael; Athanazio, Rodrigo; Fernandes, Kristianne Porta Santos; Mayer, Marcia Pinto Alves; Bussadori, Sandra Kalil; Mesquita Ferrari, Raquel Agnelli; Horliana, Anna Carolina Ratto Tempestini
Abstract : Introduction: The association between periodontal disease (PD) and chronic obstructive pulmonary disease (COPD) has been widely studied, with aspiration of periodontal pathogens being one of the most accepted causal mechanisms for pulmonary exacerbation. Periodontal treatment (PT) was associated with a decrease in these exacerbations. Bronchiectasis is a pulmonary disease that has many similarities to COPD; however, there are no studies correlating this condition to PD thus far. This study will evaluate if PT reduces proinflammatory cytokines in serum and saliva, as well as halitosis and the amount of microorganisms associated with exacerbation of bronchiectasis in saliva, sputum and nasal lavage 3 months after PT. Methods and analysis: A total of 182 patients with PD and bronchiectasis will be randomly allocated to group 1 (positive control; scaling and root planing (SRP)+oral hygiene (OH)) or group 2 (experimental; SRP+photodynamic therapy+OH). After 3 months, samples of saliva, nasal lavage and sputum will be collected to determine the level of Pseudomonas aeruginosa, Staphylococcus aureus and Porphyromonas gingivalis by quantitative PCR. This protocol will determine the efficacy of PT in reducing the most likely niches of bronchiectasis exacerbation by comparing pre- and post-treatment microbiology samples. Furthermore, there will be assessment of oral halitosis and verification of inflammatory cytokines in serum and saliva. Ethics and dissemination: This protocol has been approved by the Research Ethics Committee of Universidade Nove de Julho. Data will be published in a peer-reviewed journal. Trial registration number: NCT02514226.